2004
DOI: 10.1016/j.aca.2003.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscosity on droplet formation and mixing in microfluidic channels

Abstract: This paper characterizes the conditions required to form nanoliter-sized droplets (plugs) of viscous aqueous reagents in flows of immiscible carrier fluid within microfluidic channels. For both non-viscous (viscosity of 2.0 mPa s) and viscous (viscosity of 18 mPa s) aqueous solutions, plugs formed reliably in a flow of water-immiscible carrier fluid for Capillary number less than 0.01, although plugs were able to form at higher Capillary numbers at lower ratios of the aqueous phase flow rate to the flow rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
262
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(274 citation statements)
references
References 23 publications
7
262
0
5
Order By: Relevance
“…Higher values of Ca > 0.1 result in laminar, continuous flow of immiscible fluids instead of discrete plug formation. 81 We have found that an equilibrium surface tension at the fluorous-aqueous interface of 10-20 mN m −1 is optimal for plug formation of aqueous protein and buffer solutions with viscosities close to that of water. All surfactants used in this study gave acceptable plug formation.…”
Section: Resultsmentioning
confidence: 96%
“…Higher values of Ca > 0.1 result in laminar, continuous flow of immiscible fluids instead of discrete plug formation. 81 We have found that an equilibrium surface tension at the fluorous-aqueous interface of 10-20 mN m −1 is optimal for plug formation of aqueous protein and buffer solutions with viscosities close to that of water. All surfactants used in this study gave acceptable plug formation.…”
Section: Resultsmentioning
confidence: 96%
“…The ratio of flow rates (Q ¼ Q d =Q c ) and the viscosity ratio (k ¼ g d =g c ) are two important dimensionless numbers to characterize the droplet breakup, which has been confirmed by a wide range of experimental and numerical investigations. 18,19,23,25,26,37,57 The geometrical parameters, w c , w d , and h, lead to two additional dimensionless parameters characterizing the geometry. One is the ratio of the channel depth to the inlet width of the continuous phase (C ¼ h=w c ), and the other is the ratio of the inlet widths of the two phases (K ¼ w d =w c ).…”
Section: -3mentioning
confidence: 99%
“…1) made in glass polydimethylsiloxane (PDMS) by using soft lithography technology (Duffy et al 1998). When two immiscible fluids are injected, various flows such as droplets, pearl neacklaces, disordered patterns or parallel flows can be obtained after the junction (Squires and Quake 2005;Thorsen et al 2001;Tice et al 2004;Guillot and Colin 2005;Guillot et al 2007). However, in a wide range of flow rates, the two immiscible fluids flow side by side forming a laminar parallel flow.…”
Section: Principle Of the Microrheometermentioning
confidence: 99%